The Effect of Turmeric Drink and Lavender Aromatherapy Combination on Neck Pain in Batik Craftsmen in Tuban - Dwi Wulandari, Indriani; Harmayetty, Harmayetty (Fundamental and Management Nursing Journal, 2021)
Neck pain in batik craftsmen causes discomfort to work so the efficiency and productivity decrease. Neck pain in batik craftsmen is caused by a bent position when sitting for a long time and done by sitting in a small chair which is usually called a dingklik. The process of canting takes 6-8 hours per day so that the batik craftsmen have a short rest time which causes fatigue and muscle tension. The research objective was to analyze the effect of the combination of turmeric water and lavender aromatherapy on neck pain in batik craftsmen. The research design used was pre-experimental using one- group pre-post test data collection method with a sample size of 74 respondents. Samples were taken using probability sampling techniques. The independent variable in this study is the combination of turmeric water and lavender aromatherapy. The dependent variable in this study was neck pain in batik craftsmen. The instrument in this study used a demographic data questionnaire, a numeric rating scale pain measurement sheet and standard operating procedures for making turmeric water and lavender aromatherapy. The research data obtained were analyzed by Wilcoxon Signed Rank Test αâ‰¤0.05. There is an effect of a combination of turmeric water and lavender aromatherapy on neck pain in batik craftsmen in Tuban with a value of αâ‰¤0.05, p = 0.000. The combination of turmeric water and lavender aromatherapy can reduce the level of neck pain in batik craftsmen with neck pain complaints.